HOLISTIC VISION OF POST-BIRTH DEPRESSION (CIPEEX, 2022)
THE PRESENT ARTICLE AIMED TO DESCRIBE THE EPIDEMIOLOGY INVOLVED IN THE HEALTH-DISEASE PROCESS OF POSTPARTUM DEPRESSION, ITS CONSEQUENCES, ITS RISK FACTORS, ITS FORMS OF TREATMENT AND PROPHYLAXIS. IT IS AN INTEGRATIVE REVIEW OF THE LITERATURE, IN WHICH THE DESCRIPTORS USED WERE "DEPRESSION", "POSTPARTUM", "PSYCHOLOGICAL", WITH THEIR RESPECTIVE CORRESPONDENTS IN ENGLISH. POSTPARTUM DEPRESSION IS A CLINICAL CONDITION THAT IN BRAZIL AFFECTS 10-15% OF PUERPERAL WOMEN AND INTERFERES WITH THE WELL-BEING OF WOMEN, THE RELATIONSHIP BETWEEN MOTHER AND CHILD, THE LINK BETWEEN THE TWO, WHICH CAN LEAD TO PROBLEMS IN THE DEVELOPMENT. WOMEN WITH EPISODES OF LIFE-LONG DEPRESSION OR PREVIOUS POSTPARTUM DEPRESSION, WHO USED ALCOHOL OR TOBACCO DURING PREGNANCY AND THOSE WHO BECAME PREGNANT IN AN UNPLANNED MANNER, HAVE THESE CHARACTERISTICS AS RISK FACTORS FOR THE DEVELOPMENT OF POSTPARTUM DEPRESSION . AS AN OPTION OF TREATMENTS, WE HAVE THE PSYCHOLOGICAL PRENATAL, WHICH SEEKS TO PROVIDE EMOTIONAL SUPPORT, COGNITIVE BEHAVIORAL THERAPY, WHICH AIMS TO HELP THE PATIENT TO SOLVE THEIR BEHAVIOR BY LEARNING AND COGNITIVE RESTRUCTURING, AND PHARMACOLOGICAL THERAPY IN WHICH IT IS PRESCRIBED ANTIDEPRESSANTS, MOOD STABILIZERS, ANTICONVULSANTS, ANTIPSYCHOTICS AND BENZODIAZEPINES. THE HIGH PREVALENCE OF POSTPARTUM DEPRESSION FOUND IN TODAY'S SOCIETY REINFORCES ITS SIGNIFICANCE AS A PUBLIC HEALTH PROBLEM. THEREFORE, THIS DISEASE SHOWS THAT IT IS NECESSARY TO DEVELOP PREVENTION AND TREATMENT STRATEGIES. CAREFUL MONITORING OF MOTHERS, ESPECIALLY LOW-INCOME MOTHERS, CAN PREVENT SERIOUS PERSONAL AND FAMILY PROBLEMS ARISING FROM PPD.
Keywords: Depression. Post childbirth. Disorder.